Randomized controlled trial of a pilot PrEP linkage intervention for individuals leaving incarceration in a southern state: Design and baseline characteristics. - Heather Horton; S Alexandra Marshall; Mofan Gu; Brooklyn Tody; Timikia Jackson; Nick Zaller (PLoS ONE)
Objective We report baseline characteristics of a pilot intervention, PrEP-Link, which uses a community health worker (CHW) model to provide navigation to PrEP, the daily HIV preventative medication, and other medical and social services upon release from incarceration. Trial design and methods This pilot study uses a randomized controlled trial design. The control group receives enhanced standard of care, and the intervention receives enhanced standard of care plus personalized navigation services from the CHW for up to one year. PrEP-Link is modeled after the Transitions Clinic Program, where a CHW who has lived experience of incarceration builds close relationships with individuals and community partners. After COVID-19 restrictions prevented recruitment within local jails, recruitment for this study took place in local reentry centers which house individuals as they near completion of their jail or prison sentence. Data are collected at baseline, 6 months, and 12 months. Planning and reporting was guided by the CONSORT 2010 checklist. Results We enrolled 80 participants between September 2021 and April 2023. Thirty-nine participants were assigned to the control group and forty-one to the intervention group. Data collected at baseline included measures of PrEP usage, HIV risk, drug and alcohol use, healthcare usage, and history of incarceration. Analysis of baseline characteristics show comparability of both demographic and HIV-related risk factors between the two arms. Conclusions At baseline, participants had high clinical indication for potential PrEP benefit, particularly with respect to self-reported intravenous drug use and condomless sex. Participants responded with high PrEP acceptability within both study arms. Participants reported low preventative healthcare utilization at baseline. Barriers to accessing PrEP among the study population are significant. Results of this pilot RTC will help inform CHW lead PrEP-linkage interventions for people leaving incarceration.